The Toyota way to service excellence lean transformation in service organizations - Liker, Jeffrey K.; Ross, Karyn (McGraw-Hill Education, 2017)
The world's bestselling Lean expert shows service-based organizations how to go Lean, gain value, and get results-The Toyota Way . A must-read for service professionals of every level, this essential book takes the proven Lean principles of the bestselling Toyota Way series and applies them directly to the industries where quality of service is crucial for success. Jeff Liker and Karyn Ross show you how to develop Lean practices throughout your organization using the famous 4P model. Whether you are an executive, manager, consultant, or frontline worker who deals with customers every day, you'll learn how take advantage of all Lean has to offer. With this book as your guide, you'll gain a clear understanding of Lean and discover the principles, practices and tools needed to develop people and processes that surprise and delight each of your customers. These ground-tested techniques are designed to help you make continuous improvements in your services, streamline your operations, and add ever-increasing value to your customers. Fascinating case studies of Lean-driven success in a range of service industries, including healthcare, insurance, financial services, and telecommunications, illustrate that Lean principles and practices work as well in services as they do in manufacturing. Drawn from original research and real-world examples, The Toyota Way to Service Excellence will help you make the leap to Lean.
Includes bibliographical references and index. - Print version record
Keywords: Toyota Jidōsha Kabushiki Kaisha -- Management; Automobile industry and trade -- Management -- Japan; Lean manufacturing -- Japan; Toyota Jidōsha Kabushiki Kaisha; Automobiles; Industrie et commerce; Japon; Gestion; Production allégée; Japon; BUSINESS & ECONOMICS; Production & Operations Management; Automobile industry and trade; Management; Lean manufacturing; Management; Japan